Performance Measurement and Incentive Intensity - Alberto Bayo-Moriones; Jose Enrique Galdon-Sanchez; Sara Martinez-de-Morentin (Institute for the Study of Labor (IZA), 2015)
This study addresses the factors that determine the intensity of pay for performance schemes. The results indicate that the use of individual and group incentives boost intensity, whereas plant or firm pay for performance do not seem to affect the variable of interest. In addition, the adoption of measures of results, such as productivity or quality, has a significant positive effect on intensity. On the contrary, measures of human resource management outcomes, subjective measures and financial measures are not significant or have a negative effect on the intensity of pay for performance.
Keywords: J30; M52; M12; 330; pay for performance